Effectiveness Of Peppermint Aromatherapy To Minimize Shortness Of Breath In Patients With Pulmonary Tuberculosis - Nunung Nurhayati; Eva Supriatin; Linlin Lindayani (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis with various symptoms. It spreads through droplets of people infected with TB bacilli. Patients with pulmonary TB have several different complaints that can exacerbate respiratory difficulties, including shortness of breath. Inhalation is a form of treatment by supplying steam ventilation directly to the respiratory tract. EBN is developed to assess the potency of aromatherapy peppermint to minimize shortness of breath in patients with pulmonary tuberculosis. This EBN uses literature-based approaches to analyze study findings collected from method article filter searches using Google Scholar and PubMed databases. Results revealed that the use of peppermint aromatherapy was successful against shortness of breath in patients with pulmonary tuberculosis.